The Effect of Ration Supplementation for Lactating Ewes with Protected Fats and Conjugated Linoleic Acid on Some Blood Parameters in Suckling Lambs - Alexandru Grigorescu; Sorin Voia; Ioan Peţ; Iulia Tudora; Ionela Hotea; Adela Marcu; Călin Julean; Ducu Sandu Ştef; Nicolae Păcală; Marioara Nicula; Adrian Grozea; Lavinia Ştef (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of this study was to quantify the effect that the Optima 100 nutritional supplements (protected fats) and CLA (conjugated linoleic acid) administered in the ration of mother sheep during lactation had on blood indices in lambs during lactation. The experimental period began immediately after lambing and lasted for 60 days. 40 sheeps were grouped as follows: The control group (CG) received only the basic ration (BR); In experimental group 1 (EG1) the basic ration was supplemented with 12 g/head/day with the product Optima 100 which represents protected fats; In experimental group 2 (EG2), BR was supplemented with CLA in an amount of 12 g/head/day. The two nutritional supplements were added to BR, each in an amount of 12 g/head/day, to experimental group 3 (EG3). The values obtained in EG1 lambs were significantly (p<0.05) lower for TP, BUN and TBLI, significantly higher (p<0.05) for TCHO, TG, HDL, LDL, GPT, GOT and LIP, and insignificant (p>0.05) for GLU. For the lambs in group EG 2 the parameters were significantly (p<0.05) lower for GLU and BUN, significantly higher (p<0.05) for TCHO, TG, HDL, LDL, GPT, GOT and LIP, and insignificant (p>0.05) for TP and TBIL. By combining the two supplements for group EG3, the blood parameters were significantly (p<0.05) lower for LDL, GLU, BUN and TBLI, respectively significantly higher (p<0.05) for TCHO, TG, HDL, TP, GPT, GOT and LIP.